The influence of local administration of simvastatin in calvarial bone healing in rats - Calixto, Jimmy Cavalcanti; Villaboim de Castro Lima, Carlos Eugenio; Frederico, Lilian; dos Santos de Castro Lima, Rafaela Pio; Anbinder, Ana Lia [UNESP] (Churchill Livingstone, 2011)
Some authors have associated the use of statins, hypolipidemic drugs, and new bone formation. The aim of this work was to evaluate the effect of locally administered simvastatin on bone healing. Bone calvarial defects 5 mm in diameter were made in 64 rats. The animals were divided into four groups according to the graft material: the control group, in which the defects were not treated, the SIM-1 group, which received a sponge of collagen soaked with simvastatin (2.2 mg/50 mu l), the SIM-2 group, which received a sponge of collagen soaked with simvastatin (0.5 mg/50 mu l), and the carrier (CAR) group, which received a sponge of collagen and water. The animals were sacrificed after 30 or 60 days. The skulls were removed, and radiographic clensitometry and histometric analyses of the bone defect area were performed. Local crust formation was clinically verified in SIM-1 and SIM-2 animals. After statistical analysis (p < 0.05) of bone area data, we observed no significant differences among the groups after 30 days. After 60 days, however, there was less bone formation in the CAR and SIM-2 groups. The SIM-2 group also presented with lower radiographic densities after 60 days. According to the methodology used, we conclude that locally administered simvastatin was detrimental to the repair of defects in the calvaria of rats. (C) 2010 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: simvastatin; bone repair; densitometry; histomorphometry